Skripsi PENGARUH LATIHAN CROSS COUNTRY TERHADAP DAYA TAHAN AEROBIK ATLET SEKOLAH SEPAKBOLA (SSB) PAGARUYUNG FC KECAMATAN TANJUNG EMAS KABUPATEN TANAH DATAR - heru asrian; Apri Agus (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2019)
Abstract: The research problem is still not good Aerobiks Resistance of Football School (SSB) Athlete Pagaruyung FC Tanjung Emas District Tanah Datar Regancy. This study aims to determine the effect of Cross Country Training on Aerobiks Resistance of Football School (SSB) Athlete Pagaruyung FC Tanjung Emas District Tanah Datar Regancy. This type of research is experimental research. The population in this study were all Football School (SSB) Athlete Pagaruyung FC Tanjung Emas District Tanah Datar Regancy amounting to 37 people. The sampling technique is a purposive sampling technique, samples taken at the (final youth) level 15 to 20 years totaling 20 people. Data collection was carried out by conducting a pre-test and post-test of the Aerobiks Resistance Football School (SSB) Athlete Pagaruyung FC Tanjung Emas District Tanah Datar Regancy using the Yo-Yo Intermitten Recovery Test. Data analysis and hypothesis testing using comparative analysis techniques using different mean test formula (t test) with a significance level α = 0.05. From the data analysis carried out the results obtained: There is an effect of Cross Country training on Aerobik Endurance of Football School (SSB) Athlete Pagaruyung FC Tanjung Emas District Tanah Datar Regancy.